Evaluation of Discipline-Specific Outcomes Through a Multidisciplinary Team Clinic for Patients With Isolated Cleft Palate. (November 2021) - Trivedi, Prerak B.; Padovano, William M.; Skolnick, Gary B.; Menezes, Maithilee D.; Grames, Lynn M.; Cheung, Susan; Kim, Andrew M.; Cradock, Mary M.; Naidoo, Sybill D.; Snyder-Warwick, Alison K.; Patel, Kamlesh B.
Objective: To describe the incidence and timing of provider-specific interventions for children with isolated cleft palate. Design: This was a retrospective cohort study involving review of medical records. Setting: Multidisciplinary team care clinic at a tertiary academic children's hospital between January 2000 and July 2019. Patients: Patients with isolated nonsyndromic cleft palate seen by an American Cleft Palate-Craniofacial Association-approved team; 138 children were included. Main Outcome Measures: Study outcomes included incidence of secondary velopharyngeal management, tympanostomy tube insertion, speech therapy, hearing loss, dental/orthodontic treatment, and psychology interventions. Provider-specific outcomes were calculated for patients at ages 0 to 3, 3 to 5, and >5 years. Results: Median follow-up time was 7.0 years (interquartile range: 3.3-11.8 years). At their last team assessment, 42% of patients still had conductive hearing loss. The rate of tympanostomy tube insertions not done alongside a palatoplasty was highest for ages 3 to 5 and dropped after new American Academy of Otolaryngology-Head and Neck Surgery Foundation guidelines in 2013 ( P = .015); 54% of patients received speech-language therapy during follow-up. Palatoplasty, psychology, and dental/orthodontic treatment were all less common than speech or ENT treatment ( P < .01). Secondary palatoplasty was performed in 31 patients (22%). Patients who received speech, dental/orthodontic, or psychology intervention followed up longer than those who did not (9.8 vs 2.1 years, P < .001). Conclusion: Half of the patients terminated team follow-up by age 7, suggesting that burden of care outweighed perceived benefits of continued follow-up for many families. These results can be used to adjust protocols for children with isolated cleft palate.